(untitled) - Momsen, Janet Hensall (London, 2010)
This is the most useful and comprehensive volume to have been published in the field of gender and development. The intellectual rigour combined with accessibility and engagement makes it a critical read for students, researchers, academics and policy makers. Indeed anyone who wishes to gain an in-depth yet wide ranging understanding of key contemporary global issues within the gender and development arena should read this book
Keywords: Women in development,Phụ nữ và phát triển; Developing countries,Quốc gia đang phát triển